A REALIDADE DE UMA COMUNIDADE NEGRA RURAL DE PONTA GROSSA/PR EM CONTEXTO ESCOLAR: IDENTIDADE NEGRA E RACISMO - Nascimento, Evelise dos Santos do (2014)
Munanga (2008a) thinks that "education can offer both young people and adults the possibility to question and deconstruct myths of superiority and inferiority among human groups created by the racist culture in which they socialized (MUNANGA,2008a, p. 13). Thus, it is seen that it is necessary to reflect upon racism in schools, once this practice cannot be justified since it is not in accordance with human rights. On the other hand, it is important to understand that it is our duty as citizens to contribute to the deconstruction of the racial democracy myth. Therefore, the object of this study was the Law 11.645/08 that made the teaching of Afro-Brazilian and local Indian culture and history compulsory in public and private schools all over the country. The main aim was to analyze the comprehension teachers, teaching staff and students' mothers who work with or live near black students in the rural black community of Sutil have(PALMARES..., 2014) in relation to the Law and the black identity, through the discourse they produce. More specifically, the focus was on the teachers and teaching staff's comprehension of the law and its relevance to the school; observe the existing relation between community and school regarding the treatment the school gives to racism and thus notice how the school deals with racism, as well as to observe whether the mothers who take part in the study and their children face racism at the school. The theoretical background comprises Fernandes (2008); Munanga (2004; 2005; 2008a;2008b; 2010; 2012); Muniz (2009; 2010; 2011); Praxedes (2010); Raim (2011); Silva,Ana Lucia (2012); Silva, Ana Célia (2008); Silva, Consuelo Dores (1995); Silva, Petronilha (2008); Ziviani (2012), among others. Qualitative research was chosen as it is a study involving complex issues which involves value judgement and a case study was developed in order to answer the research questions. The results obtained suggest that: a) teachers do not notice or do not understand the relevance of the Law; b) the rural black community of Sutil understands that it is the school responsibility to work racial issues related to the Afro-Brazilian culture; c) the school has not solved racism related issues; d) the mothers of the community notice the presence of racism at the school and the importance of the school action in relation to this issue.